Cultures of Eschatology Volume 1: Empires and Scriptural Authorities in Medieval Christian, Islamic and Buddhist Communities : Volume 2: Time, Death and Afterlife in Medieval Christian, Islamic and Buddhist Communities - Wieser, Veronika; Eltschinger, Vincent; Heiss, Johann; Wieser, Veronika; Eltschinger, Vincent; Heiss, Johann (Berlin/Boston De Gruyter, 2020)
The belief in the Last Things has an integral place in Christianity, Islam, and Buddhism. The two volumes want to explain how eschatological thought influenced and factored into the political and religious perception and self-definition of medieval communities. How did notions of an imminent end shape a community$1 (Bs identity, the perception of other communities and an individual$1 (Bs perspective towards life and the world?s
Austrian Science Fund
English
Keywords: Middle Eastern history; Medieval history; Social & cultural history; History of religion; Church history; Medieval history; apocalypticism; messianism; eschatology; End-Time scenarios